Optimizing Macronutrients in People with Diabetes - Gupta, Lovely; Lal, Priti Rishi; Khandelwal, Deepak (Journal of Social Health and Diabetes, 2018)
Diverse dietary practices and nutritional counseling strategies are followed in the management of diabetes and its comorbidities. The dietary approaches practiced in India make use of calorie and nutrient counting to ensure patient-centered nutrition therapy in diabetes management. Macronutrient modulation is a central pillar of patient-centered medical nutrition therapy (MNT). Carbohydrates (CHO) are considered as the predominant macronutrient affecting postprandial blood glucose levels. The insulin-to-CHO ratio is used for calculating mealtime insulin doses among patients on insulin regimen. The aim of this article is to highlight challenges faced in planning MNT, modifying recommended dietary allowances for persons with diabetes, and suggesting solutions to overcome these. It also aims to understand the requirement of individual macronutrients and their impact on glycemia as well as insulin dose adjustment.
Keywords: nutritional recommendations; medical nutrition therapy; macronutrients; carbohydrates; fats; proteins; nutritional requirements; blood glucose concentrations; insulin dose adjustments; glycemic control